PENGEMBANGAN MATERI AJAR BILINGUAL PADA MATERI PERSEGI, PERSEGI PANJANG, DAN SEGITIGA BERBASIS REALISTIC MATHEMATIC EDUCATION (RME) DI KELAS III SEKOLAH DASAR - Trisha Ramadhani Salam; Jesi Alexander Alim; Neni Hermita (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2022)
This research is a development research (R&D) which aims to develop bilingual teaching materials on square, rectangular, and triangle-based material based on RME (Realistic Mathematical Education) in grade III Elementary. This study uses the Plomp model with the research subjects of third grade students at SD Negeri 011 Kembang Harum. The development of teaching materials is carried out in 3 phases; preliminary research, development or prototype, and assessment. Data collection techniques are interviews and questionnaires. The validation of teaching materials was carried out by 3 experts; material experts, educational technology experts, and language experts. The validation results from the three experts or validators show that the bilingual teaching material on the RME-based square, rectangular, and triangular materials obtained an average percentage of 90.55% with the "very valid" category. Practicality tests were conducted on teachers and students. The results from students obtained an average percentage of 96% in the "very practical" category and from teachers obtained an average percentage of 92% in the "very practical" category. Based on the results of the validation and practicality obtained, it can be concluded that the bilingual teaching materials on the square, rectangular, and triangular materials developed meet the valid and practical criteria.